Discard composition associated with the deep water rose shrimp fisheries (Parapenaeus longirostris, Lucas 1846) in the south-central Mediterranean Sea - MILISENDA, G.; VITALE, S.; MASSI, D.; ENEA, M.; GANCITANO, V.; GIUSTO, G. B.; BADALUCCO, C.; GRISTINA, M.; GAROFALO, G.; FIORENTINO, F. (Mediterranean Marine Science, 2017)
Discarding in fisheries is believed to be a waste of natural resources, as it is the part of the total catch brought on board but then returned to the sea dead or alive for any reason. This study aims to advance knowledge of the discards associated with the deep water rose shrimp fisheries in the south-central Mediterranean Sea. We address this issue by examining the data collected within the module of commercial catch monitoring (Campbiol) of European data collection framework (DCF) between January 2009 and December 2013. Multivariate data analysis and the generalized additive model (GAMs) were used to assess the spatio-temporal composition of the discard and factors influencing its distribution. Overall, discard represented 32.9±15.4% of the total catch. Multiple analysis of variance highlighted the significant effect on discard assemblage only for the factor of depth (p-value <0.05). In general, bony fish were the most discarded organisms (23.5±14.4%). Cartilaginous fish, crustaceans and other invertebrates represented approximately 13% of the total catch. The fraction of discard in the catch presented significant variation regarding the years, depth and fishing ground. Our results showed that most of the discards in the deep water rose shrimp (DPS) fisheries are due to species that have a minimum legal size (Hake, DPS, Trachurus spp.), and are consequently subjected to the discard ban (art. 15 of the reg. EU 1380/2013). To avoid the landing of discards, specific measures aimed to minimize the unwanted catches of undersized species should be implemented.